Peluang Bisnis Kantong Belanja Ramah Lingkungan Berbasis Pada Perilaku Konsumen Ritel Modern akan kantong Plastik Berbayar - ., Suharmiati; Harni, Budi (Jurnal Ilmiah Manajemen Kesatuan, 2017)
This study aims to determine the behavior of modern retail consumers will use plastic bags in shopping at modern retail stores Indonesia. The second goal of this research is to know consumer perception of product and price from environmentally friendly shopping bag packaging product. The third objective is to know the business opportunity of environmentally friendly shopping bags. Samples were chosen using non-probability technique ie convenience sampling with sample size was 194 respondents. Data collection techniques used questionnaire instruments with data analysis techniques using descriptive data analysis and non-parametric paired sample comparison analysis methods. Based on the results of the analysis datadiketahui that consumer behavior is the respondents of this research is not or have not moved to take the initiative to carry their own shopping bags, when shopping at modern retail stores.